Self-Employment and Wage Earning: Hungary During Transition - Catherine Y. Co; Ira N. Gang; Myeong-Su Yun (Institute for the Study of Labor (IZA), 2002)
We examine the earnings determinants of the self-employed and wage earners in Hungary in the mid-1990's, taking into account two forms of selection: selection into working or nonworking for every individual in our sample and selection into self-employment or wageearning jobs for workers only. Previous studies use switching regression to examine the returns to individual characteristics taking into account only selection into self-employment or wage-earning jobs. We find that the estimated returns to individual characteristics when accounting for both forms of selection differ from estimates correcting for only selection into self-employment or wage-earning jobs. We also find that the earnings determinants of the two sectors are not significantly different from one another.
Keywords: P23; J31; C34; 330; self-selection; switching; self-employment; wage-earning jobs; economies in transition; Selbständige; Einkommen; Lohn; Übergangswirtschaft; Schätzung; Ungarn; self selection; Selbstselektion